Synthesis and crystal structure of 2,2,2-trichloroethyl N-{4-[6-(1-hydroxyethyl)-1,2,4,5-tetrazin-3-yl]benzyl}carbamate - J. Voss; H.G. Stammler; N. Sewald (Acta Crystallographica Section E: Crystallographic Communications)
An orthogonally addressable 3,6-disubstituted 1,2,4,5-tetrazine, namely 2,2,2-trichloroethyl N-{4-[6-(1-hydroxyethyl)-1,2,4,5-tetrazin-3-yl]benzyl}carbamate (C14H14Cl3N5O3), was synthesized and characterized by single-crystal X-ray diffraction. The tetrazine comprises a free hydroxyl and a 2,2,2-trichloroethoxycarbonyl protected amino group, which gives rise to hydrogen-bonding interactions each making the tetrazine highly linked in the solid state. The carbamate moieties form intermolecular hydrogen bonds, stacking the tetrazine molecules above each other, while lateral hydrogen bonds are formed between a tetrazine N atom and a hydroxyl group, the latter interaction being a scarcely explored structural feature of 1,2,4,5-tetrazines.